2016
DOI: 10.1016/j.aogh.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Intake, Blood Pressure, and Dietary Sources of Sodium in an Adult South Indian Population

Abstract: In a South Indian population, the dietary intake of sodium was higher than recommendations by major dietary guidelines and was an independent predictor of SBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 21 publications
4
33
0
1
Order By: Relevance
“…These studies are summarized in Table . The outcomes examined were diverse: one study assessed mortality outcomes (category I), two studies assessed morbidity outcomes (category II), two studies assessed outcomes related to symptoms/quality of life/functional status (category III), six studies assessed BP outcomes (category IV), seven studies assessed other clinically relevant surrogate outcomes (category V), and 10 studies assessed physiologic outcomes (category VI) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies are summarized in Table . The outcomes examined were diverse: one study assessed mortality outcomes (category I), two studies assessed morbidity outcomes (category II), two studies assessed outcomes related to symptoms/quality of life/functional status (category III), six studies assessed BP outcomes (category IV), seven studies assessed other clinically relevant surrogate outcomes (category V), and 10 studies assessed physiologic outcomes (category VI) …”
Section: Resultsmentioning
confidence: 99%
“…No primary research studies in the physiologic category (category VI) met the minimum methodological criteria. A range of outcomes were captured by the studies considered to be of lower quality, including all‐cause mortality, headaches/migranes, BP, cognitive function, acne, obesity and ghrelin, multiple sclerosis, BMD, gastric cancer, flow‐mediated dilatation, pulse wave velocity, markers of the renin‐angiotensin‐aldosterone system, heart rate, insulin resistance and the metabolic syndrome, brain tissue white matter hyperintensity, uric acid, and urinary albumin . Most of these studies found adverse effects of dietary salt on health, except for three that were neutral and one that found an inverse relationship between salt intake and headaches/migranes …”
Section: Resultsmentioning
confidence: 99%
“…However, the reach to Asian Americans, who have high sodium intakes, 12 may be limited for two reasons. First, the primary sources of sodium consumed in Asian Americans appear to be salt added during cooking, not from packaged and restaurant foods; 13,31,32 and second, Asian Americans may retain traditional dietary practices postmigration to America. 33,34 Examination of Asian American demographics in NHANES reveals that NHANES appears to have recruited one portion of this population: highly educated, high-income earners 35,36 -with these individuals likely being more acculturated, 37 meaning they have adopted more US cultural practices.…”
Section: Dietary Sources Of Sodium Nhanes 2011-12 -Firestone Et Almentioning
confidence: 99%
“…39,40 Data from Asia indicates that high sodium intake exists across Asian subgroups. 11,32 Although rigorous methods were used for dietary recall that allow for incorporation of diverse dietary patterns, a lack of representativeness for ethnic diets in FNDDS food codes may have resulted in misclassification, and data are subject to measurement error (ie, recall and coding errors). A validation study using 24-hour urinary sodium as the reference measure found differential misreporting of sodium intake by sex and BMI, but not race/ethnicity, although the sample was not large enough to allow for an Asian American subcategory.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The association between high daily sodium intake and hypertension is known and considered an important factor in the genesis of hypertension. 43 Notwithstanding, the reduction or adequacy of daily sodium intake is recommended as a primary intervention for patients with hypertension, 5,6 owing to the evidence that nutritional adequacy leads to reduction in BP levels. 44 The fact that the magnitude of BP increase or decrease differs among the population to changes in sodium load has led to the search for genes related to sodium sensitivity.…”
Section: Ace Gene I/d Polymorphism and Hypertension In The Populationmentioning
confidence: 99%